2015
DOI: 10.1021/acs.langmuir.5b01549
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Controlled Properties of Myosin Studied by Electric Field Modulation

Abstract: The efficiency of dynamic nanodevices using surface-immobilized protein molecular motors, which have been proposed for diagnostics, drug discovery, and biocomputation, critically depends on the ability to precisely control the motion of motor-propelled, individual cytoskeletal filaments transporting cargo to designated locations. The efficiency of these devices also critically depends on the proper function of the propelling motors, which is controlled by their interaction with the surfaces they are immobilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Thus, Sundberg et al 24 proposed that a rougher surface may cause a decrease in the sliding velocity due to friction or a nonuniform HMM surface density. Furthermore, van Zalinge et al 47 suggested that chemical interactions of the forceproducing HMM motor domains with protruding parts of the surface may cause a decrease in sliding velocity with increased surface roughness. However, Albet-Torres et al 22 did not detect clear differences in motility quality between surfaces with different roughnesses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Sundberg et al 24 proposed that a rougher surface may cause a decrease in the sliding velocity due to friction or a nonuniform HMM surface density. Furthermore, van Zalinge et al 47 suggested that chemical interactions of the forceproducing HMM motor domains with protruding parts of the surface may cause a decrease in sliding velocity with increased surface roughness. However, Albet-Torres et al 22 did not detect clear differences in motility quality between surfaces with different roughnesses.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the differences in velocity between TU7 and CSAR 62 and the similarities between TMCS and TU7 support the view that also other factors than the contact angle and surface roughness are important. 14,21,22,47 More detailed studies in the future as previously performed for other polymer materials 21,48 would be of value, e.g., analyzing the difference in water uptake and polymer mechanical properties at the macromolecular chain level. In this connection it is of interest 21 to investigate if there are differences in total HMM density as well as in the fraction of active HMM molecules on the different polymers.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of surface in single-molecule optical tweezers studies is thus important. In addition to surface hydrophobicity also surface charge [ 98 , 99 ] and nanomechanical properties of the surface may be of relevance [ 100 , 101 , 102 ].…”
Section: Challenges In Single-molecule Mechanicsmentioning
confidence: 99%
“…It is known that the movement of filaments is not restricted to a certain direction when HMM molecules are randomly fixed on glass slides without orientation [1]. At the same time, alignment of the movement of filaments was observed when an external electric field was applied to the motility system [5,6]. Therefore, the filament velocity in our system with voltage application may also have been affected by electrophoresis, which can attract actin filaments toward an anode.…”
Section: Increase and Decrease In Velocity In The Vicinity Of Voltagementioning
confidence: 78%
“…In addition to their importance for muscular physiology, the ability of these complexes to generate force and transport vesicles in vivo can potentially drive micro-devices [3,4]. In the context of motility control, the movement of actin filaments interacting with myosin motors fixed on a glass slide, which is referred to as "in vitro motility assay", can be aligned when a direct or alternating current electric field is applied to the system [5,6]. In addition, the velocity can be enhanced using micro-heater, conductive polymers, or conductive glass [7e9], although these methods are lacking in terms of active switching off of the motility.…”
Section: Introductionmentioning
confidence: 99%